Expert Testimony, Law and Epistemic Authority. Issue 2 (29th March 2016) - Ward, Tony
Abstract: This article discusses the concept of epistemic authority in the context of English law relating to expert testimony. It distinguishes between two conceptions of epistemic authority (and epistemic deference), one strong and one weak, and argues that only the weak conception is appropriate in a legal context, or in any other setting where reliance on experts can be publicly justified. It critically examines Linda Zagzebski's defence of a stronger conception of epistemic authority and questions whether epistemic authority is as closely analogous to practical authority as she maintains. Zagzebski elucidates a kind of deference that courts generally, and rightly, try to avoid. Her concept of 'first person reasons', however, does capture an important aspect of the deliberations of conscientious legal actors.